Transient Simulation to Analyze Wax Deposition and Flow Pattern Behavior Along Tubing Under Esp Installation and Gassy Well Condition - Brian Tony; Steven Chandra; Rafael J.S. Purba; Muhammad Fadhlan Solihan; Ega Dimas Saputra (Testing Center for Oil and Gas LEMIGAS, 2025)
Wax deposition is a common phenomenon that restricts flow in tubing, causing production decline. In the studied well, this decline is linked to wax thickness increasing from 0.0021 inches (Day 1) to 0.0114 inches (Day 7), occurring as fluid temperatures drop below 153.5°F. An Electrical Submersible Pump (ESP) is used to address this, but it impacts thermal conditions and flow behavior, especially in gassy wells. Therefore, a transient simulation is required to analyze wax deposition and flow behavior under ESP installation. This study performs a 7-day transient simulation using OLGA 2022.1.0 on the